Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

If f(x) = 3x^2 + 4x-5, then f(-2) =

Sagot :

f(x) = 3x² + 4x - 5

So, f(-2)

= 3(-2)² + 4(-2) - 5

= 3(4) + (-8) - 5

= 12 - 8 - 5

= 4 - 5

= -1

Answer:

-1

Step-by-step explanation:

[tex]f(x) = 3x {}^{2} + 4x - 5 \\ f( - 2) = 3( - 2) {}^{2} + 4( - 2) - 5 \\ = 12 - 8 - 5 \\ = - 1[/tex]